2015
DOI: 10.1590/1678-775720150268
|View full text |Cite
|
Sign up to set email alerts
|

Can a bleaching toothpaste containing Blue Covarine demonstrate the same bleaching as conventional techniques? An in vitro, randomized and blinded study

Abstract: Objective The purpose of this in vitro study was to compare the efficacy of a bleaching toothpaste containing Blue Covarine vs. conventional tooth bleaching techniques using peroxides (both in-office and at-home).Material and Methods Samples were randomly distributed into five experimental groups (n=15): C - Control; BC – Bleaching toothpaste containing Blue Covarine; WBC – Bleaching toothpaste without Blue Covarine; HP35 - In-office bleaching using 35% hydrogen peroxide; and CP10 – At-home bleaching with 10% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 14 publications
(24 reference statements)
1
24
0
1
Order By: Relevance
“…Use of spectrophotometer for this purpose in our study was similar to previous studies. 22,23 However, some other studies measured the change in color by analyzing digital images or use of a colorimeter. 1,18,24,25 In the present study, different toothpastes caused color change in acceptability threshold or out of acceptability threshold after 90 days (Z350 showed perceivable color change after brushing with the conventional toothpaste for 90 days and Z250 showed perceivable color change after brushing with the whitening toothpaste for 90 days).…”
Section: Discussionmentioning
confidence: 99%
“…Use of spectrophotometer for this purpose in our study was similar to previous studies. 22,23 However, some other studies measured the change in color by analyzing digital images or use of a colorimeter. 1,18,24,25 In the present study, different toothpastes caused color change in acceptability threshold or out of acceptability threshold after 90 days (Z350 showed perceivable color change after brushing with the conventional toothpaste for 90 days and Z250 showed perceivable color change after brushing with the whitening toothpaste for 90 days).…”
Section: Discussionmentioning
confidence: 99%
“…While Collins, et al 9 (2008) and Joiner, et al 10 (2008) have demonstrated immediate, perceptible results that persist for up to 8 hours after a single application of the product, Torres, et al 12 (2013), Dantas. et al 13 (2015), Oliveira, et al 14 (2016), Horn, et al 15 (2014) and Bortolatto, et al 16 (2016) have failed to demonstrate whitening effects superior to that promoted by conventional toothpaste.…”
Section: Introductionmentioning
confidence: 99%
“…The parameter DE (total color change) for each specimen was recorded as displayed on the computer. A similarity between our current study and other studies is the use of a spectrophotometer for color measurement (Torres et al 2013;Dantas et al 2015). In contrast, other studies evaluated the color alteration by digital images or a colorimeter (Ashcroft et al 2008;Collins et al 2008, Joiner et al 2008aJoiner et al 2008b).…”
Section: Discussionmentioning
confidence: 61%